Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi Di Pabrik Teh Samijaya - Fitriana Fitriana; Barin Barlian; Arif Arif (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the simultaneous and partial effect of Leadership and Work Motivation on Work Productivity of Production Section Employees at the Samijaya Tea Factory. The research method used in this study is to use a quantitative research method with a questionnaire. The population in this study were 40 employees of the Samijaya Tea Factory production department. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of the study show that Leadership and Work Motivation simultaneously have a significant effect on the Work Productivity of Production Section Employees at the Samijaya Tea Factory. Leadership partially has a significant effect on the Work Productivity of Production Section Employees at the Samijaya Tea Factory. Work Motivation partially has a significant effect on the Work Productivity of Production Section Employees at the Samijaya Tea Factory.